Microwave Irradiation Used to Immobilize the Stationary Phase in Sol-Gel and Organic Polymer Matrix for Micro-HPLC and Capillary Electrochromatography - Zhang, Yu-Ping; Chen, Na; Zhang, Yi-Jun; Chen, Jun; Zhou, Xiao-Mao; Bai, Lian-Yang (Asian Journal of Chemistry, 2010)
A novel design to immobilize the stationary phase for micro-HPLC and capillary electrochromatography has been initially attempted. Porous temporary frit in fused silica capillary was rapidly fabricated by sintering stainless steel powders rapidly, which could withstand a high pressure up to 60 MPa during slurry packing. A mixture of monomer and porogenic solvents such as silica-based and organic-based monomers were pumped into the packed capillary, respectively, followed a quick polymerization by microwave irradiation. The sol-gel network and organic matrix were strong enough to hold back the sorbent particles in place, then rendering the end frits unnecessary. The typical columns prepared demonstrated excellent chromatographic performance using our self-installed micro-HPLC system. Baseline separation of the model analytes was achieved with the largest theoretical plate number (N) up to 40000/m for the last eluted compound (ethylbenzene), whilst a higher N over 74000/m was obtained using the solgel immobilized column by CEC. A scanning electron micrograph of a cross-section of the capillary column showed visually the morphological changes of packing material during the microwave irradiation.